Avaliação dos aspectos biológicos associados ao desenho de próteses fixas maxilares totais implantossuportadas - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
The treatment of maxillary full-arch fixed implant-supported prostheses is safe and effective, however it can present complications and many challenges for clinicians. This study evaluated the biological complications associated with maxillary full-arch fixed implant-supported prostheses (Study I), verified the relationship between the base shape of the prosthesis and biofilm accumulation, hyperemia and bone loss (Study II), and also patient satisfaction with treatment was evaluated (Studies I and II). In addition, discussed and illustrated aspects related to prosthetic planning and the correct shape of maxillary prosthesis (Study III). Studies I and II consisted of two analytical cross-sectional studies and study III is a clinical case study of a total maxillary prosthesis with 8-year follow-up period. The sample of the cross-sectional studies consisted of patients rehabilitated with implant-supported maxillary total fixed prostheses who attended to follow-up maintenance consultations at the Faculdade ILAPEO, Curitiba, Brazil. Data were collected from a questionnaire, clinical consultations and radiographic examinations between the months of May and September 2019. In study I about biological complications, 57 patients were included. From a total of 402 implants, 6 failed and 2 remained submerged, remaining 394 implants that were evaluated with a mean follow-up of 5.44 years (1-14 years). Implant survival and success rates were 98% and 91.8%, respectively. The main biological complication was soft tissue recession 21.8% (at implant level), followed by tissue hyperplasia that was observed in 8 patients (14%). Bone loss ≥ 2mm was recorded in 36 implants, and peri-implantitis index was 4.8% (19 implants). Patients who attended yearly for follow-up appointments were associated with less bone resorption compared to patients who had 2-year follow-up intervals or more. There was no significant difference in biofilm (p= 0.598) accumulation and peri-implantitis (p=0.603) index in relation to different followup appointment intervals. Study II had a sample of 56 patients (56 prostheses, 388 implants). The base of the prosthesis was divided into areas corresponding to cantilever regions and between implants regions. A total of 442 areas were analyzed, of which 58 (13.1%) were concave and 384 (86.9%) convex. Among the concave areas, 2 (3.5%) had no biofilm, in 7 (12%) the biofilm was identified with a probe, 34 (58.6%) had clinically visible biofilm and 15 (25.9%) had abundant biofilm. In the convex areas, 21 (5.5%) were biofilm free, 86 (22.4%) biofilm was detectable, 222 (57.8%) biofilm was visible and 55 (14.3%) biofilm was abundant. There was no significant difference between base formats in relation to biofilm accumulation (p= 0.066). Tissue hyperemia was observed in 199 (45%) areas and was absent in 243 (55%). The concave areas were less prone to hyperemia. Average bone loss was 0.71mm (+/- 0.91mm). Implants related to concave areas had greater bone resorption. Patients reported high level of satisfaction with treatment, but many complained about difficulty in performing hygiene procedures. Study III reported a clinical case of a rehabilitation using a total maxillary fixed prosthesis. Received allogeneic bone graft to ensure lip support, six implants and a dentogingival prosthesis installed in a immediate loading system. Case resolution was found to be effective after 8-year follow-up. The treatment of the edentulous maxilla is complex, the total implant-supported fixed rehabilitations presented biological complications, high survival rates and implant success and patient satisfaction. Base shape influenced hyperemia, and bone loss.
Keywords: Implantes dentários; Prótese dentária; Maxila; Sobrevida; Dental Implants; Dental Prosthesis; Maxilla; Survival; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA